Association of gender and knowledge in compliance of movement control order and trust in authority among public during Covid-19 / Siti Nurleena Abu Mansor, Mahanim Omar and Mawardi Omar - Abu Mansor, Siti Nurleena; Omar, Mahanim; Omar, Mawardi (2021)
Covid-19 has impacted the whole world, and it is considered a significant disaster (WHO, 2020). In Malaysia, the increase in cases of Covid-19 was reported in early March 2020, and the case spike over 4000 by 1 April 2020. As a result, the Malaysian government has taken proactive measures by conducting nationwide Movement Control Orders (MCO) under the Prevention and Control of Infectious Disease Act 1988 and the Police Act 1967 for 14 days starting 18 March 2020 (Berita Harian, 16 March 2020). MCO encircled restrictions on movement, assembly, and international and local travel. Other regulations in this order are, all religious activities were suspended, and non-essential business and services, including government and educational institutions, we're closed, to curb the spread of Covid-19 (Sukumaran, 2020). A Covid-19 MCO is a security measure that aims to minimize physical contact among individuals and groups to limit the spread of the virus (Sheik et al., 2020). During this stage, the social behaviour and social lifestyle dramatically changed among the infected countries. In the new norm, social and physical distancing are the best practices in breaking the chain of Covid-19. Since transmission of the virus is by air droplets, social distancing is an effective way to reduce the spread of the virus by keeping the distance. In addition, handwashing and wearing masks are also part of preventive procedures to prevent the virus spread from one person to another (Qian et al., 2020).